Efficiency of Tuna Marketing Channels at Kasiwa Fishing Port, Mamuju Regency, West Sulawesi - Femiliani Novitasari; Rahmat Frans Musa; Kamaruddin Kamaruddin (Jurnal Sains dan Teknologi Perikanan, 2026)
This study aims to analyze the distribution patterns, marketing margins, profits, and efficiency of the tuna marketing channel at the Kasiwa Fish Landing Site (PPI) in Mamuju Regency, West Sulawesi. The method used was a descriptive survey employing purposive sampling of 40 respondents, consisting of fishermen, distributors, port market vendors, and retail vendors. Data were analyzed using formulas for marketing margin, marketing profit, marketing efficiency (EPS), and the fisherman’s share. The results indicate six marketing channel patterns: two for tuna and four for baby tuna. For tuna, Channel I (Fishermen → Distributors) generated a margin of Rp17,000/kg with an EPS of 2.5% and a fisherman’s share of 88%, while Channel II (Fishermen → Port Market Vendors) had a margin of Rp10,000/kg with an EPS of 0.12% and a fisherman’s share of 60%. For baby tuna, Channel I has the highest fisherman’s share (45%) and is the most efficient, while the longest channels (Channels II and IV) yield the lowest fisherman’s share (33%). Overall, the marketing channels at PPI Kasiwa are considered efficient because the EPS values in all channels are below 5%. These findings imply the need for policies that encourage the strengthening of short marketing channels, increased direct access for fishermen to distributor traders, and the development of marketing infrastructure at PPI Kasiwa to maximize the share of the price received by fishermen.